2002
DOI: 10.1074/jbc.m109480200
|View full text |Cite
|
Sign up to set email alerts
|

Creation of an Allosteric Phosphofructokinase Starting with a Nonallosteric Enzyme

Abstract: An allosteric phosphofructokinase (PFK) was created by sequence manipulation of the nonallosteric enzyme from the slime mold Dictyostelium discoideum (DdPFK). Most amino acid residues proposed as important for catalytic and allosteric sites are conserved in DdPFK except for a few of them, and their reversion did not modify its kinetic behavior. However, deletions at the unique C-terminal extension of this PFK produced a markedly allosteric enzyme. Thus, a mutant lacking the last 26 C-terminal residues exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 52 publications
3
20
0
Order By: Relevance
“…These results agree with recent findings obtained by mutations of the non-regulatory PFK from Dictyostelium discoideum, which suggested that the action of the inhibitor MgATP is decoupled from Fru-6-P co-operativity, and that stimulation by Fru-2,6-P 2 operates on the same R/T conformational transition that accounts for co-operativity [20]. These results agree with recent findings obtained by mutations of the non-regulatory PFK from Dictyostelium discoideum, which suggested that the action of the inhibitor MgATP is decoupled from Fru-6-P co-operativity, and that stimulation by Fru-2,6-P 2 operates on the same R/T conformational transition that accounts for co-operativity [20].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results agree with recent findings obtained by mutations of the non-regulatory PFK from Dictyostelium discoideum, which suggested that the action of the inhibitor MgATP is decoupled from Fru-6-P co-operativity, and that stimulation by Fru-2,6-P 2 operates on the same R/T conformational transition that accounts for co-operativity [20]. These results agree with recent findings obtained by mutations of the non-regulatory PFK from Dictyostelium discoideum, which suggested that the action of the inhibitor MgATP is decoupled from Fru-6-P co-operativity, and that stimulation by Fru-2,6-P 2 operates on the same R/T conformational transition that accounts for co-operativity [20].…”
Section: Discussionsupporting
confidence: 92%
“…Auxiliary enzymes were desalted as described [20]. In all cases, the reaction was started after a 5-min preincubation by the addition of Fru-6-P, and was followed by measuring the absorbance change at 340 nm at 25 • C. When PFK activity was assayed during purification, glucose 6-phosphate was added to Fru-6-P in proportions of 3:1 (mol/mol).…”
Section: Enzyme Activity Assaymentioning
confidence: 99%
“…Human muscle PFK-M and Dictyostelium discoideum PFK were expressed in S. cerevisiae strain HD152-1D carrying deletions in both yeast PFK genes (10), and the recombinant proteins were purified and assayed as described previously (29,30). Protein concentration was determined by the Bradford dye binding method (31), using bovine ␥ globulin as standard.…”
Section: Enzyme Purificationmentioning
confidence: 99%
“…The effect of Fru-1,6-P 2 was examined as described (27). Auxiliary enzymes were desalted as described (29). Fructose-1,6-bisphosphatase and fructose-2,6-bisphosphatase activities were measured as described by Aragón et al (30), except that the pH was 7.0 and Fru-1,6-P 2 concentration was 50 M, and by González-Mateos et al (31), respectively.…”
Section: Methodsmentioning
confidence: 99%